Transcend the Current Debate on Administrative Theory - Gordon, Paul (Academy of Management Journal, 1963)
The article discusses several important aspects of administrative theory, including the traditional approach, behavioral approach, decisional approach, and ecological approach. A discussion is presented about the emphasis and hallmark characteristics of each approach. Details related to their concepts and tools are examined. The author provides an explanation for the multiple approach of administrative theory. An overview of challenges associated with building an administrative theory is presented.